The possible role of methylglyoxal metabolism in cancer - Khalid O. Alfarouk; Saad S. Alqahtani; Saeed Alshahrani; Jakob Morgenstern; Claudiu T. Supuran; Stephan J. Reshkin (Journal of Enzyme Inhibition and Medicinal Chemistry, 2021)
Tumours reprogram their metabolism to acquire an evolutionary advantage over normal cells. However, not all such metabolic pathways support energy production. An example of these metabolic pathways is the Methylglyoxal (MG) one. This pathway helps maintain the redox state, and it might act as a phosphate sensor that monitors the intracellular phosphate levels. In this work, we discuss the biochemical step of the MG pathway and interrelate it with cancer.